Making waves in cancer research: new models in the zebrafish. (August 2005) - Berghmans, Stephane; Jette, Cicely; Langenau, David; Hsu, Karl; Stewart, Rodney; Look, Thomas; Kanki, John P.
The zebrafish ( Danio rerio ) has proven to be a powerful vertebrate model system for the genetic analysis of developmental pathways and is only beginning to be exploited as a model for human disease and clinical research. The attributes that have led to the emergence of the zebrafish as a preeminent embryological model, including its capacity for forward and reverse genetic analyses, provides a unique opportunity to uncover novel insights into the molecular genetics of cancer. Some of the advantages of the zebrafish animal model system include fecundity, with each female capable of laying 200–300 eggs per week, external fertilization that permits manipulation of embryos ex utero, and rapid development of optically clear embryos, which allows the direct observation of developing internal organs and tissues in vivo. The zebrafish is amenable to transgenic and both forward and reverse genetic strategies that can be used to identify or generate zebrafish models of different types of cancer and may also present significant advantages for the discovery of tumor suppressor genes that promote tumorigenesis when mutationally inactivated. Importantly, the transparency and accessibility of the zebrafish embryo allows the unprecedented direct analysis of pathologic processes in vivo, including neoplastic cell transformation and tumorigenic progression. Ultimately, high-throughput modifier screens based on zebrafish cancer models can lead to the identification of chemicals or genes involved in the suppression or prevention of the malignant phenotype. The identification of small molecules or gene products through such screens will serve as ideal entry points for novel drug development for the treatment of cancer. This review focuses on the current technology that takes advantage of the zebrafish model system to further our understanding of the genetic basis of cancer and its treatment.